The impact of non-additive genetic associations on age-related complex diseases - Marta Guindo-Martínez (Nature Portfolio, 2021)
Most genome-wide association studies assume an additive model, exclude the X chromosome, and use one reference panel. Here, the authors implement a strategy including non-additive models and find that the number of loci for age-related traits increases as compared to the additive model alone.